Penguatan Kesiapan Psikologis Mahasiswa Menghadapi Kuliah Kerja Nyata Melalui Diskusi Interaktif - Hilman Syarif; Jufrizal Jufrizal; Andara Maurissa (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
Students who will attend community service program often experience psychological disorders, such as worry and anxiety. This community service project aims to lowering the worry and anxieties of students who will carry out community service program. The target of this activity is students of the sixth semester of undergraduate programs at the Faculty of Nursing, Universitas Syiah kuala. The activity was carried out within 90 minutes by online method in 64 students. Interactive discussions were conducted after participants were briefed about self-efficacy and empathy behavior, as well as self-talk activities as interventions to lowering worry and anxiety. Evaluation is done by providing opportunities for participants to self-reflection and dissemination of satisfaction level questionnaires through google form. As a result, after an interactive discussion, students said worry and anxiety were reduced and made self-talk as an effort to lowering worry and anxiety. The satisfaction poll showed 64% of participants were very satisfied and 36% were satisfied with this activity. In conclusion, interactive discussions are beneficial for lowering worry and anxiety. Recommendations, increased satisfaction of participants can be improved by face-to-face methods.